Temperature‐dependent regulation of the Ochrobactrum anthropi proteome. Issue 23 (December 2016) - Varano, Mariaconcetta; Gaspari, Marco; Quirino, Angela; Cuda, Giovanni; Liberto, Maria Carla; Focà, Alfredo
Abstract : Ochrobactrum anthropi is a Gram‐negative rod belonging to the Brucellaceae family, able to colonize a variety of environments, and actually reported as a human opportunistic pathogen. Despite its low virulence, the bacterium causes a growing number of hospital‐acquired infections mainly, but not exclusively, in immunocompromised patients. The aim of this study was to obtain an overview of the global proteome changes occurring in O . anthropi in response to different growth temperatures, in order to achieve a major understanding of the mechanisms by which the bacterium adapts to different habitats and to identify some potential virulence factors. Combined quantitative mass spectrometry‐based proteomics and bioinformatics approaches were carried out on two O. anthropi strains grown at temperatures miming soil/plants habitat (25°C) and human host environment (37°C), respectively. Proteomic analysis led to the identification of over 150 differentially expressed proteins in both strains, out of over 1200 total protein identifications. Among them, proteins responsible for heat shock response (DnaK, GrpE), motility (FliC, FlgG, FlgE), and putative virulence factors (TolB) were identified. The study represents the first quantitative proteomic analysis of O. anthropi performed by high‐resolution quantitative mass spectrometry.